The MuPix sensor for the Mu3e experiment - Augustin, Heiko; Schöning, André; Weber, Alena (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2020)
The Mu3e experiment will search for the charged lepton flavor violating decay μ+→e+e−e+ with an ultimate sensitivity of one in 1016 decays (in phase II). To reach this sensitivity, a momentum resolution of 0.5MeV/c and a vertex resolution of about 200 μm is required. The particle rate is given by more than 109 muon stops per second. To achieve the specifications, High Voltage Monolithic Active Pixel Sensors (HVMAPS) are used for all layers of the tracking system. The chip developed for Mu3e is called MuPix. In the last years, several prototypes have been designed and tested. By the end of 2019, the next large MuPix - MuPix10 - was submitted and represents a final version prototype. MuPix10 is based on a 180 nm HVCMOS process. The matrix consists of 250× 256 pixels with a size of 80× 80 μm2. The total chip size is 20.66× 23.18mm2. All hits are read out using a continuous readout system. The signal is amplified in the pixel and transmitted as an analogue signal to the readout cell located in the chip periphery, where it is discriminated by two comparators.